Planned birth at 39 weeks in low-risk nulliparous women: mapping international evidence to India's national health mission framework - Deepa V. Mungi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Global obstetric practice has shifted over the past decade from routine expectant management of low-risk term pregnancies toward active consideration of planned birth at 39 weeks, while India's public health system has, over the same period, achieved substantial gains in institutional delivery, antenatal coverage, and high-risk pregnancy tracking under the National Health Mission (NHM). This review synthesizes the international evidence for planned 39-week birth in low-risk nulliparous women, examines the small emerging Indian evidence base, weighs areas of continuing debate around implementation and external validity, and maps the resulting picture onto the operational architecture of PMSMA, LaQshya, and SUMAN. International randomized and cohort evidence consistently favors planned 39-week birth, with reduced caesarean delivery and reduced hypertensive disorders of pregnancy; the largest available cohort found a substantial reduction in perinatal mortality for planned birth overall, though this benefit was driven predominantly by scheduled caesarean rather than induction specifically. Two Indian trials identified to date, both small, point in the same direction as the international literature and do not show any caesarean-increasing effect of induction. Real-world implementation data complicate a purely reassuring picture, raising legitimate questions about indication creep, external validity, and systemic workload. The more consequential India-specific finding is infrastructural rather than physiological: national first-trimester registration has risen sharply, but this reflects administrative registration rather than confirmed dating ultrasound, making gestational-age precision the central prerequisite for any 39-week protocol in India. A phased approach, gated on confirmed dating and supported by prospective audit, offers a measured pathway for evaluating this practice in the Indian context.